도시 중년여성의 스트레스에 따른 영양 섭취와 대사증후군의 관련성 - 변수지(Suji Byeon); 신윤진(Yoonjin Shin); 윤정원(Jungwon Yoon); 김수아(Sooa Kim); 김양하(Yangha Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구는 한국 중년 여성을 대상으로 신체적･정신적 건강에 영향을 미치는 스트레스 수준을 평가하고, 스트레스 정도에 따른 영양 섭취 상태 및 대사증후군의 위험도를 조사하고자 수행되었다. 한국인유전체역학조사사업의 일환인 도시기반코호트를 이용하여 대도시 및 중소도시 지역의 40~64세 중년 여성을 대상으로 하였다. 스트레스 수준을 평가하기 위해 사회심리적웰빙지수를 이용하였으며, 총점 27점을 기준으로 저스트레스군(70,873명)과 고스트레스군(10,756명)으로 나누어 비교하였다. 고스트레스군은 저스트레스군에 비해 음주와 흡연을 하는 비율이 높았으며, 규칙적으로 운동하는 비율과 교육 및 수입 정도는 낮은 것으로 나타났다. 고스트레스군은 당화혈색소, 공복혈당, 중성지방의 농도가 높았지만, 총콜레스테롤, HDL 콜레스테롤 및 LDL 콜레스테롤 농도는 낮았다. 영양 섭취 상태를 조사한 결과 고스트레스군은 저스트레스군에 비하여 탄수화물의 섭취량은 많았지만, 열량, 단백질, 비타민 및 무기질 등 탄수화물을 제외한 나머지 영양소의 섭취량은 적었다. 고스트레스군은 복부비만, 높은 중성지방, 높은 공복혈당을 포함한 대사증후군의 교차비가 유의적으로 높게 나타났다. 또한 탄수화물 섭취량이 많을수록 대사증후군의 교차비가 증가했으며, 지방, 레티놀 및 비타민 E의 섭취량이 많을수록 교차비는 감소하였다. 결과적으로 한국 중년 여성에서 스트레스가 높을수록 탄수화물의 섭취가 많았으며 대사증후군 위험이 증가하는 것으로 나타났다. This study was conducted to investigate whether stress is associated with nutritional intake and risk of metabolic syndrome in urban middle-aged women. Subjects were participants from the Health Examinee Study, which was a part of the Korean Genome and Epidemiology Study. According to scores of the Psychosocial Well-being Index-Short Form, a total of 81,629 subjects were classified into a low stress group (n=70,873, 0 to 26 points) and a high stress group (n=10,756, ≥27 points). Dietary intake was assessed by a semi-quantitative food frequency questionnaire. The high stress group showed higher intake of carbohydrates and lower intake of other nutrients compared to the low stress group. Subjects with high stress also showed a higher odds ratio (OR) of metabolic syndrome (OR: 1.09, 95% confidence interval (95% CI): 1.03∼1.16), including abdominal obesity (OR: 1.06, 95% CI: 1.01∼1.11), elevated triglyceride (OR: 1.11, 95% CI: 1.05∼1.18), and elevated fasting glucose (OR: 1.08, 95% CI: 1.02∼1.14), compared to those with low stress levels. Moreover, there were increasing trends in the OR of metabolic syndrome with higher intake of carbohydrate (OR: 1.30, 95% CI: 1.20∼1.41). These results suggest that stress might partially increase metabolic syndrome in middle-aged women with high carbohydrate intake. KCI Citation Count: 8